2011
DOI: 10.1007/s11920-011-0250-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes in Borderline Psychopathology: Old Assumptions, Current Findings, and New Directions

Abstract: Borderline personality disorder (BPD) and historical variants of the diagnosis were long held to represent an intractable syndrome of psychopathology consisting of interpersonal, intrapsychic, and affective disturbances. For years, patients labeled "borderline" were regarded pejoratively due at least in part to the lack of effective treatments. Prospective data from recent naturalistic follow-along studies along with the development of treatments with empirically demonstrated efficacy have changed how BPD is v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 69 publications
0
11
0
1
Order By: Relevance
“…About 10% of all patients with borderline personality disorder diagnosis commit suicide [20,21], with higher rates in studies with longer follow-up [22]. Multiple suicide attempts and life-threatening self-harm behaviors are common [23] as 60 – 70% of the individuals with borderline personality disorder diagnosis attempt suicide during the course of their illness [24]. Even if the high level of suicide threats, attempts and self-injury is often seen in younger patients, the mean age of suicide completers is found to be as low as 30–37 years [8,20-22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 10% of all patients with borderline personality disorder diagnosis commit suicide [20,21], with higher rates in studies with longer follow-up [22]. Multiple suicide attempts and life-threatening self-harm behaviors are common [23] as 60 – 70% of the individuals with borderline personality disorder diagnosis attempt suicide during the course of their illness [24]. Even if the high level of suicide threats, attempts and self-injury is often seen in younger patients, the mean age of suicide completers is found to be as low as 30–37 years [8,20-22].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that this would have affected the validity of the diagnoses. The general construct validity of the personality disorder diagnoses has, however, been widely discussed [23,27,28]. Self-attributed personality traits seem to be more stable than symptoms assessed by clinicians, and diagnostic stability is generally found to be low [29].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with BPD were diagnosed with a variety of comorbid axis I and axis II disorders. In BPD, comorbidity is the rule, rather than the exception and characteristic for both adolescent and adult patients with BPD. Therefore, a sample of BPD patients with high comorbidity rates constitutes a representative, non‐artificial sample, whereas BPD patients without comorbid disorders cannot be seen as representative of the BPD population .…”
Section: Limitationsmentioning
confidence: 99%
“…BPD most often presents in late adolescence, with patients most symptomatic in young adulthood (Paris, 2003). Recent prospective studies have found that a significant majority of patients diagnosed with BPD in young adulthood will have remission at surprisingly high rates (Gunderson et al, 2000;Gunderson, Stout, & McGlashan, 2011;Skodol et al, 2005;Zanarini et al, 2005;Zanarini et al, 2006), but they continue to have challenges in employment and relationships long thereafter (Sanislow, Marcus, & Reagan, 2012;Skodol et al, 2002). In recent years a number of evidence-based interventions for BPD have been developed and tested (Bateman & Fonagy, 1999;Black, Blum, Pfohl, & St. John, 2004;Clarkin, Yeomans, & Kernberg, 2007;Linehan, 1993;McMain, Links, & Gnam, 2009;Young, 1999); at the same time, a consensus has emerged about those strategies likely to be counterproductive for this population, that is, polypharmacy, recurrent extended hospitalizations, delay in addressing borderline pathology until co-occurring Axis I disorders have remitted (American Psychiatric Association, 2001;Gunderson & Links, 2008;Oldham, 2005).…”
mentioning
confidence: 99%